Job insecurity, employability and financial threat during COVID-19 - Esther Greenglass; Lisa Fiksenbaum (Review of Economic Analysis (REA), 2023)
COVID-19 has resulted not only in widespread illness and death, it has also upended most spheres of social life including the economic/financial one in that it has had large impacts on local economies, resulting in widespread job loss, job insecurity and loss of income. Employability, a psychological construct, refers to the belief that one can get a (another) job in the event of job loss, and financial threat refers to feelings of threat and anxiety associated with one's finances. During the pandemic, many people experienced job loss due mainly to business closures. The present study examined the relationship between employability, job insecurity due to COVID-19, and financial threat in a Canadian (n= 487) and U.S. (n=481) sample of adults recruited on MTurk early on in the pandemic (April 2020). Participants in the Canadian sample, compared to their American counterparts, were less likely to be employed full-time, 37% vs. 67%, respectively, were more likely to be unemployed, 40% vs. 13%, respectively, and had lower self-reported socio-economic status. A theoretical model was put forward in which employability was associated with less job insecurity and this was related to less financial threat. Results revealed that financial self-efficacy was associated with greater employability, less job insecurity and less financial threat in both samples. Further, feelings that one had enough income to 'get by' since the advent of COVID-19, were positively related to employability in both samples, but in the Canadian sample only, these feelings were also related to less job insecurity and less financial threat. Implications of the study's results are discussed within the economic climate resulting from the pandemic.
Keywords: A12; D9; D91; J28; J62; J64; 330; COVID-19; pandemic; economic; psychological; job insecurity; job loss; financial threat